Loop electrosurgical excision procedure (LEEP) at Maharaj Nakorn Chiang Mai Hospital: problems in pathologic evaluation - Khunamornpong S. (2014)
Loop electrosurgical excision procedure (LEEP) is widely used in diagnosis and management of cervical lesions. Difficulties in histopathologic evaluation of LEEP specimens, particularly for the margin status, have been reported to be a significant disadvantage of the procedure.